Nič nie je nové pod slnkom - Baláková, Dana (Slavistična revija, 2016)
The study focuses on a cognitive-pragmatic analysis of biblical phraseology. The dynamics of biblical expressions is understood as part of the common European cultural tradition vis-a-vis their functioning in a particular socio-cultural context. The younger generations of Russian, Slovak, and German speakers exhibit differences in usage, i.e., their phraseological competence as well as their knowledge and awareness of the motivational source of biblical terms in their mother tongues. The description and interpretation of the results of the study are based on an interlinguistic comparative analysis.
Keywords: biblical expression; biblical phraseology; biblizem; frazeologija; interlinguistic comparison; medjezikovna primerjava; phraseological competency; phraseology; svetopisemska besedila